Pengetahuan dan Perilaku Pelaksanaan Protokol Kesehatan pada Mahasiswa di Era Adaptasi baru - Utami, Ressa Andriyani; Efkelin, Ria (Jurnal Kesehatan Holistic, 2022)
Introduction: the Corona Virus Diseases 19 pandemic first appeared in 2019 in Wuhan, China. Currently, Indonesia has experienced a decline in cases and the world community has been required to implement the Covid 19 protocol as a normal daily habit. Activities in all sectors began to be restored, including higher education (student activities). Objective: this research was conducted to find out how the behavior of students during the adaptation period of new habits, the influence of knowledge on Covid-19 prevention behavior and the factors that influence student behavior in preventing Covid-19. Methods: this study uses a cross sectional study approach with a total of 413 respondents, multivariate test using multiple logistic regression predictive model. Result: the results showed that there was a significant relationship between knowledge and the implementation of the Covid-19 prevention protocol in respondents (p = 0.000; = 0.05) with an OR value of 2.362. The most influential factor on the implementation of health protocols is the knowledge previously obtained from various sources (p value = 0.090). Conclusion: health promotion efforts are needed for students who will carry out normal lecture activities so as not to cause a spike in new cases in the education cluster.